Live transportation and RAM acquisition proficiency test. (March 2017) - Schramp, R.
Abstract: The content of Random Access Memory (RAM) of a computer contains forensically relevant information. However, actually acquiring it can be challenging. This article describes a proficiency test performed by several forensic laboratories and their strategies for acquiring the memory from a reference system. The proficiency test covers the full examination chain from physical crime scene to data analysis.